Farmacoeconomia ed etica: cure sostenibili e rispetto della persona - Spagnolo, Antonio G.; Minacori, Roberta (Farmeconomia. Health Economics and Therapeutic Pathways, 2004)
The scarcity of economic resources today is a fundamental problem in public healthcare. The importance of making well-founded choices for optimal resources allocation concerns also pharmacological treatments and is justified also on ethical grounds, besides the economic, political and/or medical considerations. In fact, a better management, also in economic sense, of the patient and sickness involves the possibility of offering an efficient treatment to all the sick, or at least to as many of them as possible. However, these considerations should always be subordinated to the ethical centrality of the patient, to the protection of his life, his health and his personal dignity, to the extent that life and health are priceless. The goal of ethics in pharmacoeconomics can be summarised in respect for the person, which must remain the end and reference of every therapeutic choice as well as every healthcare policy. The indispensable instruments for the realisation of the above objectives are, amongst others, those already highlighted but which demand further explanation: a) a suitable standard background/training and a multidisciplinary approach for optimising the evaluation procedures and increasing accuracy and verifiableness of the data; b) measures to contrast and disclose the conflict of interest for more transparency and credibility; c) a coherent evaluation of the ethical quality and humanness of the pharmacoeconomic analysis which requires a correct consideration of quality of life and a real respect for persons.